Biofeedback therapeutic effects on blood pressure levels in hypertensive individuals: A systematic review and meta-analysis. (August 2021) - Costa Vital, José Edimosio; de Morais Nunes, Adriele; Souza de Albuquerque Cacique New York, Beatriz; Araujo de Sousa, Barbara Dayane; Nascimento, Micaele Farias; Formiga, Magno F.; Fernandes, Ana Tereza N.S.F.
Abstract: Introduction: Systemic arterial hypertension (SAH) is considered a multifactorial disease characterized by a persistent increase in blood pressure levels. Currently, the efficient control of blood pressure is achieved by both the use of pharmacological therapy and the control of risk factors. In addition, the use of biofeedback (BFB) as a non-pharmacological strategy represents a promising therapy. Objective: This study aims to evaluate the effects of BFB on systolic and diastolic blood pressure levels, as well as on environmental and psychosocial factors in patients with essential SAH. Methods: A systematic review (SR) of the literature was carried out in English and Portuguese using the following databases: SCIELO, LILACS, CINAHL, Cochrane, and PubMed. The search strategy included a mix of terms for the key concepts Biofeedback, Heart Rate Variability, Psychophysiological Feedback, and Heart Biofeedback. Studies were analyzed independently. Results: The included studies evaluated a total of 462 subjects of both sexes. The meta-analysis revealed that BFB significantly elicited greater blood pressure control, mainly improving DBP levels (Z = 2.15; P = 0.03). Discussion: Besides improvement in DBP readings post-intervention, BFB also resulted in better disease-related environmental and psychosocial factors, such as reduced stress levels. The magnitude of effect did not appear to depend on the type of BFB applied. Conclusion: This SR demonstrated that BFB with visual and/or auditory information is a complementary option to pharmacological treatment in the management of individuals with systolic and diastolic arterial hypertension. Moreover, the use of this adjuvant therapy seems to facilitate better DPB control. Highlights: Biofeedback is a promising tool that can be used as adjuvant therapy to control BP. Biofeedback significantly elicited greater BP control, mainly improving DBP levels. Biofeedback results in improved disease-related environmental and psychosocial factors.